Does left atrial epicardial conduction time reflect atrial fibrosis and the risk of atrial fibrillation recurrence after thoracoscopic ablation? Post hoc analysis of the AFACT trial. Issue 3 (9th March 2022) - Wesselink, R; Neefs, J; van den Berg, N W E; Meulendijks, E R; Terpstra, M M; Kawasaki, M; Nariswari, F A; Piersma, F R; van Boven, W J P; Driessen, A H G; de Groot, J R
Abstract : Objectives: To determine the association between left atrial epicardial conduction time (LAECT), fibrosis and atrial fibrillation (AF) recurrence after thoracoscopic surgical ablation of persistent AF. Setting: Single tertiary care centre in the Netherlands. Participants: Patients with persistent AF from the randomised Atrial Fibrillation Ablation and Autonomic Modulation via Thoracoscopic Surgery (AFACT)-trial were included. Patients eligible for thoracoscopic AF ablation were included, full inclusion and exclusion criteria were previously published. All patients underwent thoracoscopic ablation, encompassing pulmonary vein isolation with an additional roof and trigone lesion. In patients with conduction block across the roof and trigone lesion, LAECT was measured. LAECT was defined as the time to local activation at one side of the roofline on pacing from the opposite side. Collagen fibre density was quantified from left atrial appendage histology. Outcome measures: Primary outcome: AF recurrence during 2 years of follow-up. Results: 121 patients were included, of whom 35(29%) were women, age was 60.4±7.8 and 51% (62) had at least one AF recurrence during 2 years of follow-up. LAECT was longer in patients with versus without AF recurrence (182±43 ms vs 147±29 ms, p<0.001). LAECT was longer in older patients, in patients with a higher body mass index (BMI) and in patients using class IC antiarrhythmic drugs. LAECT was shorter in patients with higher collagen fibre density. A previously failed catheter ablation, LAECT and BMI were independently associated with AF recurrence. Conclusion: LAECT is correlated with collagen fibre density and BMI and is independently associated with AF recurrence in patients with persistent AF. In these patients, LAECT appears to reflect substrate characteristics beyond clinical AF type and left atrial volume. Trial registration number: NCT01091389 .